The Effect of Different Types and Combinations of Natural Feed on The Growth and Survival of Glofish Tetra Larvae (Gymnocorymbus ternetzi) - Sigalingging, Krisda Novita; Sukendi, Sukendi; Asiah, Nur (Jurnal Akuakultur SEBATIN, 2026)
Glofish Tetra (Gymnocorymbus ternetzi) is a transgenic product of tetra fish in which a fluorescent gene from jellyfish is inserted into the fish egg genome, resulting in heritable expression of fluorescent protein. Currently, glofish is one of the most sought-after ornamental fish commodities, so it has high economic potential in the cultivation sector. The success of ornamental fish cultivation is influenced by the quality and type of feed given from the larval to broodstock phase. This study aims to determine the effect of providing different types and combinations of natural feed on the growth and survival of glofish tetra larvae. This research was conducted for 40 days in May - July 2025, located at the Fish Breeding and Cultivation Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau, Pekanbaru. The method used in this study was an experimental method using a one-factor Completely Randomized Design (CRD) with 4 treatment levels and 3 repetitions. The larvae used in the study were 7 days old and underwent feed adaptation for 2 days from the results of natural spawning carried out at the Fish Spawning and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. Feeding is done with a frequency of three times a day, namely at 08.00, 12.00, and 17.00 WIB, and is given to the larvae using the ad-satiation method. The parameters measured in this study were absolute length and absolute weight growth, larval growth rate, larval survival, larval response to feed and water quality. The results of the analysis of variance (ANOVA) test showed that providing different types and combinations of natural feed had a significant effect (P<0.05) on absolute length growth, absolute weight growth, specific growth rate and survival of glofish tetra larvae. The best treatment was P2 (AR2T4) with an absolute length of 2.34±0,01cd cm and an absolute body weight of 0.4409±0,0070c g, a specific growth rate of 2.85±0,025d %, and a survival rate of 95,00±1,67b %. The water quality in this study was classified as optimal, with temperatures ranging from 25.9 to 27.1 °C, pH 6.3 to 6.4, and DO 5.43 to 6.58 mg/L.